Potensi pengembangan desain produk bambu Kabupaten Sleman - Ismael Setiawan (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2021)
The bamboo craft industry in Sleman Regency has not experienced significant growth within the last decade. Stakeholders of the industry want to synergy with academia on design development. Design development concept associated with the design process, which requires the gathering of the information about many things associated with the products so that the created designs can solve the problem of the industry. This basic research aims to gather the information that can be the basis for the academic designer in local bamboo-based new products design engineering. The research was conducted using the qualitative method based on the interview with the craftsman, business, and multidisciplinary academia, supported by the literature study. The research concluded that the recent bamboo products design development in Sleman Regency needs to be directed to the type of product that complies with functional, uniqueness, and production efficiency aspects, especially in furniture, decoration, and interior/ exterior component products.